Comparison between Dexamethasone and Clonidine as an adjuvant to 0.5% Levobupivacaine in Supraclavicular brachial plexus block - Ritu Baloda; Kanika Rohilla; Rupali Battu (Asian Journal of Medical Sciences, 2023)
Background: Regional anesthesia avoids airway instrumentation, preserves conscious level and provide rapid recovery with significant postoperative analgesia. There has always been a search for adjuvants to the regional nerve block with drugs that prolong the duration of analgesia but with lesser adverse effects. The search for the ideal additive still continues, and therefore in this study, we investigated the effects of addition of dexamethasone versus clonidine to levobupivacaine for supraclavicular brachial plexus block. The primary outcome of this study was the onset and duration of sensory block, motor block, and the secondary outcome was postoperative analgesia. Aims and Objectives: The aim of the study was to compare the effect of dexamethasone and clonidine on onset and duration of anesthesia, when used as an adjuvant to levobupivacaine in supraclavicular brachial plexus block. 7. Materials and Methods: In this prospective, double-blind, randomized controlled trial, 60 patients with American Society of Anaesthesiologists physical status I/II scheduled to undergo upper limb surgeries below shoulder were enrolled. The patients were randomly divided into two groups: Group I (n=30): 20 mL of 0.5% isobaric levobupivacaine with 2 mL of dexamethasone. Group II (n=30): 20 mL of 0.5% isobaric levobupivacaine and 30 mcg clonidine (diluted in normal saline, making volume of 2 mL). Results: Clonidine when added to levobupivacaine provide early onset of sensory and motor block but less duration of analgesia and motor blockade as compared to dexamethasone. Conclusion: Dexamethasone should be preferred as compared to clonidine as an adjuvant whenever longer duration of post-operative analgesia is required.